Pelatihan Kader Peer Counselor untuk Meningkatkan Kebermaknaan Hidup pada Tahanan Remaja Melalui Adaptasi Seni Hikayat Aceh - Nadia Salsabila; Angelicca Erza Putri; Putri Diah Shanata; Hendry Syafrian; Faruq Miqdad Mudaffar (Fakultas Psikologi Universitas Pancasila, 2023)
This article discusses the PERKUSI (Pengenalan, Pelatihan, dan Pembinaan Kader Peer Counselor, Ekstrakurikuler Seni Hikayat Aceh, dan Pembekalan Sistem Kepengurusan dalam Organisasi) program or Introduction, Training, and Coaching of Peer Counselor Cadres, Aceh Hikayat Extracurricular, and Organizational Management System Provision, aimed at improving the meaning of life of teenage prisoners at LPKA (Lembaga Pembinaan Khusus Anak / children’s prison) Grade II Banda Aceh. The program involves introducing, training, and coaching peer counselor cadres and Acehnese hikayat extracurricular activities, as well as providing organizational management skills. The program involves 49 teenage prisoners, but only 31 of them filled out pre-test and post-test questionnaires on the meaning of life. The results showed a 93% increase in the meaning of life of teenage prisoners. The program also successfully improved the knowledge and skills of teenage prisoners regarding peer counseling and Acehnese Hhkayat art. The program also successfully formed 10 peer counselor cadres selected based on discussions with partners, knowledges and skills from pre-test and post-test results, observations during activities, and a detention period of more than four months since the peer counselor organization was established. Therefore, the PERKUSI program can be an alternative solution to the problem of meaning of life on teenage prisoners at LPKA Kelas II Banda Aceh.